Waktu Perendaman Benih Dengan Air Kelapa Mudaterhadap Pertumbuhan Bibit kakao (Theobroma cacao l.) - Saputra, Sukemi Indra; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to know the influence of seed soaking time with young coconut water on the growth of seedlings of cocoa (Theobroma cacao L.). This research has been carried out in the laboratories of the University Faculty of agriculture of Riau at Binawidya Panam 12.5 km kelurahan Simpang baru , kecamatan tampan, began from February until may 2013. This study used a Randomized Complete Design (RAL) consisting of 5 treatments (0, 6, 12, 18and 24) and three replicates. The parameters observed that high seeds, number of leaves, leaf area and stem diameter. Research results showed the cocoa seed soaking with influential real young coconut water to the seeds and leaves are wide, but has no effect against the real amount of leaf and stem diameter. Cocoa seed soaking treatment with young coconut water for 6 hours provides the best results against higher seeds parameter, the number of leaves and broad leaves. Cocoa seed soaking treatment with young coconut water for 18 hours, giving greater influence. Keywords : PGR, cacao seedling Â